(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The world’s largest young population is found in India. Positive Youth Development(PYD) is one of the models which focuses on the holistic development of youth. This model emphasizes building 5 C’s Competence, Confidence, Character, Connection, and Caring among youth. Education systems in India are developed to cater such needs. The present study is a pilot research work that focuses on comparison of CBSE and HBSE board students on 5 C’s. Objective- To study and to compare the level of Competence, Confidence, Character, Connection, and Caring of the CBSE and HBSE. Hypothesis- CBSE and HBSE board students will be different on Competence, Confidence, Character, Connection, and Caring. Method- Ex- post facto research design used for the study. 66 students of age group of 13- 16 years were selected by using the purposive sampling method from both board schools from district Gurgaon. Positive Youth Development Tool by Saha (2020) was used to collect the data. Result- Data was analyzed by using t-test. Students of both boards were found similar in competence, character, connection, and caring and significantly different in confidence. The hypothesis of the research was partially accepted as both groups of students were found significantly different only in confidence.